PENDAMPINGAN BAGI GURU PAUD KOTA BINJAI DALAM MENANAMKAN SIFAT JUJUR : STRATEGI PENERAPAN MEDIA JEPITAN JEMURAN - Rabitah Hanum; Rezki Awaliyah (Kreasi: Jurnal Pengabdian Masyarakat, 2022)
In moral attitudes and behavior, the values ​​held relate to values ​​regarding something that is said to be good and bad, right and wrong, proper and should happen. The problem with this service is that preschool children's ability to recognize honesty is still low, children are still not neat enough in cutting and sticking activities and the learning media is still limited and less interesting. The aim of this service is to interpret the results of the analysis carried out during the clothesline clamping activity process. And in this service, percentage analysis is used to obtain results regarding improving the honest nature of early childhood through the application of clothespins as media and analysis tests using child averages and criteria for children's learning completeness. The results of this service show that children are considered successful if the results achieved by the child have been achieved. reached 80% in the application of clothespins as a medium to instill honesty in early childhood